(untitled) (Progress Annals: Journal of Progressive Research, 2025)
This article examines the socio-political and economic structures of Early Medieval Sogdiana through the analysis of written and archaeological sources. Particular attention is given to the development of rural communities, landownership patterns, and the emergence of the dehqon class as a new rural aristocracy. The study explores the etymology and social function of the term naf, a kin-based community structure comparable to the modern mahalla, and its role in organizing social life. Additionally, the presence and status of slaves (qul) and the lowest social group (bantak) are discussed within the broader context of social stratification. The analysis of archival documents, including the Mount Mug archive and the Samarkand Treaty, offers valuable insights into the property relations and communal organization in Sogdiana during the early 8th century. The findings demonstrate that Early Medieval Sogd society was marked by complex layers of kinship, landholding, and hierarchical relations that significantly influenced its political and economic development